Biodegradation of N : containing aromatic compounds - Bi, Yi Fang (2015)
Synthetic organic compound is becoming a major pollution released to environment nowadays. This study focused on bio-remediation of xenobiotic organic compound 3-chloroaniline (3-CA). From previous studies, 3-CA was mainly degraded under aerobic conditions. In this study, we used bacterium strain Comamonas testosteroni WDL7 as a model and investigate the optimum condition for the bacterium strain to remediate 3-CA. C. testosteroni WDL7 is capable of reducing nitrate to nitrite under both anaerobic and micro-aerobic conditions. The nitrate reduction rate by C. testosteroni WDL7 culture with 3% oxygen in head space is faster than culture without any oxygen. High concentration of nitrate inhibits the bacteria growth and 50mg/L (NO3-N) is the optimum concentration for C. testosteroni WDL7 to respire nitrate under micro-aerobic condition. C. testosteroni WDL7 is capable of metabolizing 3-CA aerobically or micro-aerobically at 3-CA concentration level of 200 mg/L. However, the research demonstrated that the existence of nitrate has no significant influence on 3-CA degradation by C. testosteroni WDL7, and no nitrate was reduced with existence of 3-CA in medium.